Seven Dogged Myths Concerning Contingency Fees - Herbert M. Kritzer (Washington University Law Quarterly, 2002)
One of the hallmarks of litigation in the United States us what we call the supposed litigiousness of the American populace, the contingency fee is a frequent target of so-capped tort reform who seek to reduce both the exposure to lawsuits and the amounts paid out in damages. Proponents of so-called reform have propounded a variety of criticisms of contingency fees, along the way creating a variety of myths about the nature and operation of contingency fees. Here, I demonstrate that the most frequently advanced myths are just that — myths.
Keywords: Contingent fees; Advertising – Lawyers; Tort reform; Lawyers& #x27; fees